Redefining Teachers Talk Through Lesson Study - Rizkariani Sulaiman (EDU Journal - English Department of UMMU Journal, 2021)
The use of various languages ​​(Teachers Talk) in the classroom when carrying out the teaching and learning process is one of the skills needed for prospective student educators. So far, there have been many studies that discuss Teachers Talk but still partially with the practice of Lesson Study. Through a partnership program with schools, in this case English Education Study Program Universitas Muslim Indonesia with UPT SPF SMPN 23 Makassar, we observed the Teachers Talk implemented by partner teachers in four open class meetings. The whole series of learning activities is carried out by following the lesson study stages: plan, do, and see. The results of this study are that there are 7 categories of Teachers Talk displayed by the teacher when interacting in class, namely: (1) starting or opening a class; (2) provide an explanation; (3) Giving instructions; (4) Asking questions; (5) Encourage and motivate; (6) Providing Strengthening or Reinforcement; and (7) Closing the Teaching and Learning Process. The ideal Teachers Talk for students can be ordered as follows: 1) students expect to be given the opportunity to think in answering the teacher's questions; 2) students want to be given clear instructions; 3) students like being given the opportunity to speak 4) students like being given feedback and praise; 5) students like to be asked questions and answered voluntarily (without mentioning names); and 6) students like it when they are given a task in the form of problem solving (challenging). In addition, the appropriate duration of the Teaher Talk according to students is less than 15 minutes. As an improvement in lectures on campus, we developed lesson designs that meet the seven categories of Teachers' Talk and pay attention to the dominant Teachers Talk category, namely providing questions, instructions and explanations.